2006
DOI: 10.1242/dev.02535
|View full text |Cite
|
Sign up to set email alerts
|

The dwarf phenotype of theArabidopsis acl5mutant is suppressed by a mutation in an upstream ORF of a bHLH gene

Abstract: Loss-of-function mutants of the Arabidopsis thaliana ACAULIS 5 (ACL5) gene, which encodes spermine synthase, exhibit a severe dwarf phenotype. To elucidate the ACL5-mediated regulatory pathways of stem internode elongation, we isolated four suppressor of acaulis (sac) mutants that reverse the acl5 dwarf phenotype. Because these mutants do not rescue the dwarfism of known phytohormone-related mutants, the SAC genes appear to act specifically on the ACL5 pathways. We identify the gene responsible for the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
147
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(165 citation statements)
references
References 62 publications
4
147
0
3
Order By: Relevance
“…Prior to the development of Ribo-Seq, translated uORFs with regulatory functions were often identified by mutant screening or evolutionary conservation (Hill and Morris, 1993;Delbecq et al, 1994;Wiese et al, 2004;Imai et al, 2006;Hayden and Jorgensen, 2007). Although Ribo-Seq data have been used in the identification of translated uORFs (Fritsch et al, 2012;Liu et al, 2013;Ingolia et al, 2014), the application of Ribo-Seq data to the identification of ribosome stalling uORFs has not been reported.…”
Section: Investigation Of Regulatory Uorfs Using the Rna Degradomementioning
confidence: 99%
“…Prior to the development of Ribo-Seq, translated uORFs with regulatory functions were often identified by mutant screening or evolutionary conservation (Hill and Morris, 1993;Delbecq et al, 1994;Wiese et al, 2004;Imai et al, 2006;Hayden and Jorgensen, 2007). Although Ribo-Seq data have been used in the identification of translated uORFs (Fritsch et al, 2012;Liu et al, 2013;Ingolia et al, 2014), the application of Ribo-Seq data to the identification of ribosome stalling uORFs has not been reported.…”
Section: Investigation Of Regulatory Uorfs Using the Rna Degradomementioning
confidence: 99%
“…Exogenous application of thermospermine or norspermine was able to rescue the acl5 phenotype. Furthermore, thermospermine or norspermine upregulated ATHB8, PHB, and SAC51, a gene encoding a bHLH transcription factor found from the suppressor mutant screening of acl5 (Imai et al, 2006;Kakehi et al, 2010). Based on these, thermospermine and norspermine seem to act as signaling factors for timing xylem TE differentiation program.…”
Section: Other Small Molecules At Work In Vascular Stem Cellsmentioning
confidence: 90%
“…In eukaryotes, uORFs play important roles in translational control in response to starvation and sucrose (Raney et al 2000). A number of recent studies using heterologous or modified mRNAs have indicated that uORFs can influence more than translational efficiency (Imai et al 2006;Mehta et al 2006). In this paper, we investigated the dehydrogenase activity of AN and the possible regulation of AN expression by its uORF.…”
mentioning
confidence: 99%
“…In eukaryotes, uORFs have important roles in translational control in response to starvation and sucrose (Viese et al 2005;Raney et al 2000). In addition, a number of recent studies using heterologous or modified mRNAs have indicated that uORFs influence more than translational efficiency (Imai et al 2006;Mehta et al 2006). For instance, the sac51-d mutation, which involves a uORF in the bHLH-type transcription factor SAC51 gene, complements the dwarf phenotype of the Arabidopsis acl5 mutant as a result of increased SAC51 transcription (Imai et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation